176k views
5 votes
See the picture for the questions no

See the picture for the questions no-example-1

2 Answers

3 votes

Answer:

2( y - 1 )/y+5

Explanation:

h (y - 2) = (2 + 2 (y - 2)) / (7 +( y - 2))

=(2 +2y-4)/(7 + y -2)

=(2y -2)/(y+5)

=(2( y-1))/(y+ 5)

User Gowtham R
by
6.3k points
4 votes

Answer:


(2y-2)/(5+y)

Explanation:

Given function:


h(x)=(2+2x)/(7+x)

To find h(y - 2), substitute x = y - 2 into the given function:


\begin{aligned}x=y-2 \implies h(y-2)&=(2+2(y-2))/(7+(y-2))\\\\&=(2+2y-4)/(7+y-2)\\\\&=(2y-2)/(5+y)\end{aligned}

User Yoselin
by
5.6k points